Barriers to Organizational Change and How to Overcome Them - Sitora Narmuradova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Many changes are happening in every type of organization from year to year. Changes leads to organizations develop, regenerate technologies, increase efficiency and effectiveness and make better working conditions. Also, it affects to design, strategies and planning in workplace.